The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/gerona/63.4.391
|View full text |Cite
|
Sign up to set email alerts
|

The Physical and Biological Characterization of a Frail Mouse Model

Abstract: These physical and biological findings suggest that the IL-10(tm/tm) mouse develops inflammation and strength decline consistent with human frailty at an earlier age compared to C57BL/6J control type mice. This finding provides rationale for the further development and utilization of the IL-10(tm/tm) mouse to study the biological basis of frailty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 22 publications
2
136
0
1
Order By: Relevance
“…Cause–effect relationship will be important, given the result of clinical studies that found that inhibiting certain inflammatory cytokines, for example, TNF‐α, had no impact on mortality in the setting of HFrEF (Coletta et al ., 2002). Investigators have found that mice that are deficient in IL‐10, an immune suppressive cytokine, exhibit some clinical features of frailty, specifically declining muscle strength by 14 months of age as compared to age‐matched wild‐type controls (Walston et al ., 2008). This study represents a potential murine model of frailty; however, it is confounded as IL‐10‐deficient mice exhibit signs of inflammatory bowel disease (Davidson et al ., 2000), which could explain the features described in the study.…”
Section: How To Examine the Mechanisms Of Frailty Experimentallymentioning
confidence: 99%
“…Cause–effect relationship will be important, given the result of clinical studies that found that inhibiting certain inflammatory cytokines, for example, TNF‐α, had no impact on mortality in the setting of HFrEF (Coletta et al ., 2002). Investigators have found that mice that are deficient in IL‐10, an immune suppressive cytokine, exhibit some clinical features of frailty, specifically declining muscle strength by 14 months of age as compared to age‐matched wild‐type controls (Walston et al ., 2008). This study represents a potential murine model of frailty; however, it is confounded as IL‐10‐deficient mice exhibit signs of inflammatory bowel disease (Davidson et al ., 2000), which could explain the features described in the study.…”
Section: How To Examine the Mechanisms Of Frailty Experimentallymentioning
confidence: 99%
“…Downregulation of the apoptotic pathway can reduce the decline in muscle mass and function in aged animals (Dirks & Leeuwenburgh, 2004; Marzetti et al ., 2009). Upregulation of the apoptotic pathway has been identified in premature aging models including mice lacking the antioxidant enzyme copper/zinc‐dependent superoxide dismutase (CuZnSOD or Sod1) that exhibit accelerated sarcopenia (Jang et al ., 2010), as well as interleukin‐10‐deficient mice that exhibit extreme frailty (Walston et al ., 2008). Increased levels of DNA laddering and caspase‐3 activity have been observed in transgenic mice expressing defective mitochondrial polymerase (Hiona et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The IL10 tm/tm mice develop an age-related increase in SM weakness, inflammation and increased mortality compared to age-matched B6 mice and thus have been proposed as a model of human frailty (Walston et al 2008;Ko et al 2012). We report here, for the first time, that in vivo SM energy metabolism is deranged at rest in frail IL10 tm/tm mice as evidenced by a decline in intracellular [PCr], accumulation of P i , together with a decrease in the rate of ATP synthesis via CK (i.e., CK flux) and in the unidirectional rate of ATP synthesis from P i as compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-two-week-old male IL-10 deficient (IL10 tm/tm ) and age-and sex-matched C57/BL6 (B6) mice were used for this study. Strength and activity decline with age in IL10 tm/tm mice, as compared to control mice, and mortality is increased at this age (Walston et al 2008;Ko et al 2012). IL10 tm/tm mice were homozygous for the IL10 tm/Cgn targeted mutation and were fully backcrossed on B6 background (Kuhn et al 1993).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation